The Determinants of Punishment: Deterrence, Incapacitation and Vengeance - Bruce Sacerdote
Does the economic model of optimal punishment explain the variation in the sentencing of murderers? As the model predicts, we find that murderers with a high expected probability of recidivism receive longer sentences. Sentences are longest in murder types where apprehension rates are low, and where deterrence elasticities appear to be high. However, sentences respond to victim characteristics in a way that is hard to reconcile with optimal punishment. In particular, victim characteristics are important determinants of sentencing among vehicular homicides, where victims are basically random and where the optimal punishment model predicts that victim characteristics should be ignored. Among vehicular homicides, drivers who kill women get 56 percent longer sentences. Drivers who kill blacks get 53 percent shorter sentences.